PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS WEB PADA MATA PELAJARAN BAHASA JAWA MATERI UNGGAH-UNGGUH BASA UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS VIII SMP NEGERI 1 JABON - Jannah, Farotul; Retno Danu Rusmawati; Hartono, Hartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of technology, information and communication is increasingly rapid. The impact of its development can also be felt in the world of education, including the creation of various IT-based learning media that can help teachers in the learning process. In its development, the new curriculum is Digital Simulation. Analysis of data in the field and preliminary studies, researchers stated that at SMP Negeri 1 Jabon, generally using textbooks (Print) teaching materials as a companion to the learning process, computer-based teaching materials are also not used very often, especially Javanese language subjects, especially basic uploaded materials. . Apart from that, for local content subjects (Mulok), the time allocation is only 1 hour of class. Therefore, it is necessary to implement learning using Web-based e-learning media. The development stages of Web-based E-Learning Learning Media use the ADDIE model, because it is a development model that is easy to implement and has structured and very clear stages in its implementation. The results of this e-learning development research were declared suitable for use based on the assessment of content/learning material experts and learning media design experts as well as the results of the assessment recap of small group trials and large group trials. So, based on the results of this research, it is stated that the development of web-based e-learning learning media in Javanese language subjects with Basa uploaded material is declared feasible and can be used in future learning.